Multiple supratentorial and infra -tentorial cavernous hemangiomas in a 5 year–old girl - Eslamiyeh, Hossein; Eslamiyeh , Zahra (Iranian Journal of Child Neurology, 2023)
Cavernous hemangiomas (CHs) are vascular structures comprising of clusters of abnormally dilated blood vessels. It is estimated to occur this anomaly in approximately one out of every 500-600 people,. Individuals often show the first sign of cavernous hemangiomas in their second or third decade of life therefore, the presentation of this disorder is not common in children, here we presented a 5 year-old-girl who developed abruptly nearly fixed right sided eyes deviation and incoordination after a short course of viral infection. In physical examination, she had left peripheral facial palsy in addition to right eye oculomotor nerve and left abducens nerve palsy. A computed tomography (CT) scan of her brain revealed hemorrhages in posterior aspect of the pons and some areas of hemispheres in different stages. Following brain magnetic resonance imaging, multiple popcorn ball low-signal T2* lesions with both supra- and infra tentorial location with marked peripheral hypo intensities were seen. These findings were in favor of multiple cavernous hemangiomas of the brain. The novelity of our case was due to observing cavernous angiomas in both supra and infra tentorial spaces in pediatric age.